Photochemical box modelling of volcanic SO2 oxidation: isotopic constraints - T. Galeazzo (Atmospheric Chemistry and Physics, 2018)
The photochemical box model CiTTyCAT is used to analyse the absence of oxygen mass-independent anomalies (O-MIF) in volcanic sulfates produced in the troposphere. An aqueous sulfur oxidation module is implemented in the model and coupled to an oxygen isotopic scheme describing the transfer of O-MIF during the oxidation of SO2 by OH in the gas-phase, and by H2O2, O3 and O2 catalysed by TMI in the liquid phase. Multiple model simulations are performed in order to explore the relative importance of the various oxidation pathways for a range of plausible conditions in volcanic plumes. Note that the chemical conditions prevailing in dense volcanic plumes are radically different from those prevailing in the surrounding background air. The first salient finding is that, according to model calculations, OH is expected to carry a very significant O-MIF in sulfur-rich volcanic plumes and, hence, that the volcanic sulfate produced in the gas phase would have a very significant positive isotopic enrichment. The second finding is that, although H2O2 is a major oxidant of SO2 throughout the troposphere, it is very rapidly consumed in sulfur-rich volcanic plumes. As a result, H2O2 is found to be a minor oxidant for volcanic SO2. According to the simulations, oxidation of SO2 by O3 is negligible because volcanic aqueous phases are too acidic. The model predictions of minor or negligible sulfur oxidation by H2O2 and O3, two oxidants carrying large O-MIF, are consistent with the absence of O-MIF seen in most isotopic measurements of volcanic tropospheric sulfate. The third finding is that oxidation by O2∕TMI in volcanic plumes could be very substantial and, in some cases, dominant, notably because the rates of SO2 oxidation by OH, H2O2 and O3 are vastly reduced in a volcanic plume compared to the background air. Only cases where sulfur oxidation by O2∕TMI is very dominant can explain the isotopic composition of volcanic tropospheric sulfate.